The influence of manufacturing strategy on firm's level strategy, external environment and international performance: The case of Malaysian furniture industry. - Ismail, Noor Azlin; Othman, Mohd Shahwahid (2012)
Malaysia has always been known for its wood based manufacturing products including furniture, owing to its natural resources. In 2009, Malavsia was the 10d] largest exporter of furniture indeed it was 3rd in Asia and 2nd amongst the Association of Southeast Asia Nations (ASEAN). This industry is highly fragmented and the predominance of the small and medium enterprises (SMEs) in the industry is very significant. Generally, the sectoral patterns of the wooden furniture industry have been consistently postulated as low tech, labour intensive and supplier dominated. In the context of market globalization, furniture manufacturers attempt to differentiate their products to attain competitive advantages, From past studies, Original Equipment Manufacturing (OEM), Original Design Manufacturing (ODM) and Own Brand Name (OBN) were among main manufacturing strategies enabling such differentiation. For many years, Malaysia has mainly focused on producing as an OEM, and the industry was perceived as a low-end market manufacturer producing according to the design and specifications of importing customers. Building from a few relevant theories, a theoretical framework is proposed to investigate the relationship among OEM, ODM, OBN with firm level and external environments. The result of this study will reveal the current status of this industry after the global recession that brought a severe contraction in 2009.